Effective restoration of partial nitritation and anammox biofilm process by short-term hydroxylamine dosing: Mechanism and microbial interaction. (December 2021) - Huang, Ting; Zhao, Jianqiang; Hu, Bo; Zhao, Junkai; Yuan, Chunbo
Graphical abstract: Highlights: PN-A biofilm process could be restored effectively by NH2 OH dosing. NOB repression by NH2 OH dosing was reversible under over aeration. NH2 OH dosing promoted the production of NO and N2 O in PN-A process. NO was demonstrated a product of NH2 OH oxidation in vivo. AOB and AnAOB might interact via both intermediates NH2 OH and NO. Abstract: The one-stage partial nitritation and anammox (PN-A) process frequently experiences deterioration from ammonium accumulation and nitrate build-up. In this study, hydroxylamine was dosed to restore the process from deterioration in a continuously aerated PN-A sequencing biofilm batch reactor, and the impact of hydroxylamine on the metabolism of PN-A process was studied. PN-A process was totally restored in 5 days via 10 mg N·L -1 hydroxylamine dosing, reducing nitrate-produced/ammonium-removed ratio from 28.5% to less than 11.0%. hydroxylamine dosing promoted biological production of nitric oxide and nitrous oxide and reduced the production of nitrate in the PN-A process. This study advanced the understanding of the metabolism versatility of hydroxylamine and nitric oxide as well as their function in interaction between aerobic ammonium oxidation bacteria and anaerobic ammonium oxidation bacteria, and proposed the potential application of hydroxylamine dosing in ammonium-contained wastewater treatment.